Intentional Change Model Training to Improve Leader Effectiveness of Toraja Church Youth Association (PPGT)/ Pelatihan Intentional Change Model untuk Meningkatkan Leader Effectiveness Pengurus Persekutuan Pemuda Gereja Toraja (PPGT) - Mahari, Ellyana Surya; Handoyo, Seger; Sulistyowati, Maria Eko (Psikoislamika: Jurnal Psikologi Islam, 2020)
Abstract: The effectiveness of a leader is not easy to achieve. The leader must build awareness to equip himself and his members for the achievement of objectives. Intrapersonal beliefs in their capabilities to function as leaders are called Leader Role-Efficacy (LRE), their ability to navigate and manage interpersonal relationships with their members is called Leader Trust in Subordinate (LTS), both of which are key elements of leader effectiveness. This study aims to describe whether Intentional Change Model (ICM) training can improve the leader effectiveness of PPGT administrators in the Pajalesang Palopo congregations. The subject of the study was the management of PPGT organization including fifteen people as one group pre and post-test design. The pre-test questionnaire was given a week before the treatment, and the post-test questionnaire was given two weeks after the treatment. Measuring instruments used by researchers are the Leader Effectiveness Scale by Ladegard and Gjerde and Psychological Capital Questionnaire (PCQ) by Luthans, Youssef, and Avolio. The results showed that there were significant differences in the values before and after being given the intentional change model training treatment.Keywords: Leader Effectiveness; Intentional Change Model; TrainingAbstrak: Efektivitas pemimpin bukan hal yang mudah untuk dicapai oleh pemimpin. Pemimpin harus membangun kesadaran untuk melengkapi diri dan anggotanya demi tercapainya tujuan. Keyakinan intrapersonal dalam kapabilitasnya untuk berfungsi sebagai pemimpin disebut leader role-efficacy (LRE), kemampuannya untuk menavigasi dan mengelola hubungan interpersonal dengan anggotanya disebut leader trust in subordinate (LTS), keduanya merupakan elemen kunci dari leader effectiveness. Penelitian ini bertujuan untuk memaparkan pelatihan intentional change model (ICM) dapat meningkatkan leader effectiveness pengurus Persekutuan Pemuda Gereja Toraja (PPGT) jemaat Pajalesang Palopo. Subjek penelitian yakni, pengurus organisasi PPGT berjumlah lima belas orang sebagai one group pre and post-test design. Kuesioner Âpre-test diberikan seminggu sebelum perlakuan dan kuesioner post-test diberikan dua minggu setelah perlakuan. Alat ukur yang digunakan oleh peneliti yakni Leader effectiveness scale dari Ladegard dan Gjerde dan Psychological Capital Quetionnaire (PCQ) dari Luthans, Youssef, dan Avolio. Hasil penelitian menunjukkan bahwa terdapat perbedaan signifikan nilai sebelum dan setelah diberi perlakuan pelatihan intentional change model.Kata Kunci: Efektivitas Pemimpin; Intentional Change Model; Training